I Hate Alone - Brammar, Ellen; Frewer, James (Oberon modern plays., 2017)
Every time something has gone wrong for Chloe and Danielle, every time something has been taken away, someone else has been behind it. It's time the tables turned. Righteous indignation boils over into brutal violence, driven along by a riotous soundtrack, as two best friends take aim at a world that has left them behind. Think Thelma and Louise turned up to 11, I Hate Alone is a gig with a story, about injustice, revenge and, above all, friendship.